Assessment of the Quality of Life of Patients with Coronary Heart Disease - Makhmudova Khanuza Davranovna; Khusainova Munira Alisherovna; Khaydarova Zarrina Erkinovna; KHaydarov Sanjar Nizamitdinovich (Peerian Journals Publishing, 2022)
It is known that in the analysis of the demographic situation, the concept of life expectancy is important. In recent years, WHO experts have pointed to the need to assess the quality of life of patients with socially significant diseases. Dozens of scientific papers have been published in the literature on the study of the quality of life of patients with chronic noncommunicable diseases, such as chronic lung diseases, metabolic pathology and cardiovascular diseases (CVD). The term Quality of life (Qol) first appeared in the works of social psychologists at the beginning of the XX century and was focused on assessing the degree of satisfaction of human needs. In general, the quality of life is considered as a strict scientific category. The quality of life is an integral characteristic of a person's physical, psychological and social functioning, based on his subjective perception. The quality of life acts as a prognostic indicator, since it has a close relationship with other known factors affecting the prognosis of CVD. In people with CVD, age, marital status, a history of coronary heart disease and the presence of psychological disorders have a positive relationship with the quality of life determined by the SF-36 questionnaire. On the other hand, the assessment of the quality of life allows us to indirectly judge the adequacy of the therapy and rehabilitation of patients with CVD. Some scientific papers have shown a link between improving myocardial blood supply and quality of life. Thus, coronary artery revascularization performed after acute myocardial infarction (MI) significantly improved the physical components of the quality of life
Keywords: coronary heart disease; SF-36 questionnaire; Quality of life